Domain Event Driven pada Aplikasi Komputer Catur: Logika Catur - Suprapti, Tati; Silalahi, Ryan H (KOPERTIP : Jurnal Ilmiah Manajemen Informatika dan Komputer, 2017)
Currently the chess computer has evolved in such way that many of the elements that exist in the application of computer chess can be separated and placed in another application. As an example of the chess engine that focuses only on the application’s artificial intelligence. There is also a GUI that focus solely on board and chess pieces in the absence of rules so that it can be used as another application as chess interface. By using domain event driven point of views, we can look at that elements in an application can be separated according to their domain. It's intended to define the domain rules of chess as one of the elements that can be used during the development of computer chess application. By focusing on the rules of chess as a domain we can create a library (library) application to be used as a reference by other application’s elements forming an application. The library's rules of chess can be called chess logic.